1994
DOI: 10.1002/yea.320101306
|View full text |Cite
|
Sign up to set email alerts
|

Molecular taxonomy of the yeasts

Abstract: The term 'yeast' is often taken as a synonym for Saccharomyces cerevisiae, but the phylogenetic diversity of yeasts is illustrated by their assignment to two taxonomic classes of fungi, the ascomycetes and the basidiomycetes. Subdivision of taxa within their respective classes is usually made from comparisons of morphological and physiological features whose genetic basis is often unknown. Application of molecular comparisons to questions in yeast classification offers an unprecedented opportunity to re-evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 54 publications
4
83
0
4
Order By: Relevance
“…Sequence similarities to the type strain of the closest species B. lagerstroemiae were 99.8 % in the LSU rDNA D1/D2 domain (one substitution) and 93.6 % in the overall ITS region (ITS1, 6 substitutions and 2 indels; ITS2, 7 substitutions and 3 indels), indicating that strain M9962 T is closely related to B. lagerstroemiae, but should be regarded as a separate species based on the generalization of . The DNA G+C content of strain M9962 T (42.0 mol%) was 4 mol% lower than that of B. lagerstroemiae, also suggesting separate species status (Kurtzman & Phaff, 1987). Based on these results, we concluded that our isolates represent a distinct species.…”
Section: Taxonomic Positionmentioning
confidence: 60%
“…Sequence similarities to the type strain of the closest species B. lagerstroemiae were 99.8 % in the LSU rDNA D1/D2 domain (one substitution) and 93.6 % in the overall ITS region (ITS1, 6 substitutions and 2 indels; ITS2, 7 substitutions and 3 indels), indicating that strain M9962 T is closely related to B. lagerstroemiae, but should be regarded as a separate species based on the generalization of . The DNA G+C content of strain M9962 T (42.0 mol%) was 4 mol% lower than that of B. lagerstroemiae, also suggesting separate species status (Kurtzman & Phaff, 1987). Based on these results, we concluded that our isolates represent a distinct species.…”
Section: Taxonomic Positionmentioning
confidence: 60%
“…The idea of a molecular taxonomy and DNA identification as a taxonomic tool, however, goes back earlier (e.g. KURTZMAN 1994, WILSON 1995. It is, however, most likely the demands from non-academic agencies, such as DEFRA and the resulting media attention, which has sparked renewed interest in DNA identification (i.e.…”
Section: Stakeholdersmentioning
confidence: 99%
“…The suspected Candida spp. colonies were examined using another parameters like germ tube forming and growing on corn meal agar for the production of Chlamydospores by Candida albicans as recommended by Kurtzman et al [18]. The biochemical reactions were performed according to Cruickshank et al(1994) they were concluded by using sugar fermentation and urease tests to Complete identification of different yeast isolates [19].…”
Section: Identification Of Isolated Yeast Coloniesmentioning
confidence: 99%